Dismantling Cultural Prejudice: Responses to Huntington’s Thesis in the Indonesian Media - Hendro Prasetyo (Studia Islamika, 1994)
The ideas contained in Huntington's article, "Clash of Civilization?", are provoking. Since its publication in Foreign Affairs (summer 1993), several responses have appeared in the media world-wide. In this home country, Huntington's article was critized from various angles.  His assumptions, model, data and even his potition were scrutunized mostly by social scientists and Islamicist. These criticisms, however, highlight the article's significant importance in the debates of political and cultural problems faced in the post-cold war world.DOI: 10.15408/sdi.v1i1.869